2011
DOI: 10.1093/ejo/cjq172
|View full text |Cite
|
Sign up to set email alerts
|

The monitoring of gingival crevicular fluid volume during orthodontic treatment: a longitudinal randomized split-mouth study

Abstract: Sixteen healthy orthodontic patients (7 females and 9 males; mean age, 17.7 years; range, 13-27 years) with the need for extraction of the first upper premolars were enrolled. One randomly chosen maxillary canine was subjected to a distalizing force by a 0.017 × 0.025 inch titanium-molybdenum alloy archwire and considered as the test tooth (TT). The contralateral canine, which was not subjected to any force but was included in an orthodontic appliance, was used as a control (CT). GCF sampling was performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 24 publications
4
49
0
1
Order By: Relevance
“…Here, we investigated the effect of vibratory stimuli provided by an electric toothbrush on the level of IL-1b in GCF. The GCF volumes at each time point were not significantly different between the experimental and control sites, in agreement with the findings of Drummond et al, 20 who showed that GCF volume is not a reliable biomarker of tissue remodeling during orthodontic treatment. However, in this study, the levels of IL-1b in GCF increased after application of vibratory stimuli combined with orthodontic force, even though the GCF volumes did not vary significantly between control and experimental teeth at any time point.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we investigated the effect of vibratory stimuli provided by an electric toothbrush on the level of IL-1b in GCF. The GCF volumes at each time point were not significantly different between the experimental and control sites, in agreement with the findings of Drummond et al, 20 who showed that GCF volume is not a reliable biomarker of tissue remodeling during orthodontic treatment. However, in this study, the levels of IL-1b in GCF increased after application of vibratory stimuli combined with orthodontic force, even though the GCF volumes did not vary significantly between control and experimental teeth at any time point.…”
Section: Discussionsupporting
confidence: 91%
“…The GCF volumes at each time point were of low statistical relevance in differences between the conventional and experimental groups, in agreement with the findings of Drummond et al (31) and Leethanakul et al (16) who showed that GCF volume is not a reliable biomarker of tissue remodeling during orthodontic treatment. Hence, it seems reasonable to continue using quantity of GCF only as a measurement necessary for estimating concentration of biomarkers into GCF and not for direct assumptions on orthodontic tooth movement.…”
Section: Discussionsupporting
confidence: 90%
“…Van Gastel et al [21], in their study, have examined periodontal parameters at the beginning of orthodontic treatment at and 3 month after the removal of brackets and reported that GCF volume increased at the removal of the brackets compared with baseline and that this volume is still higher than baseline 3 months later. Drummond et al [29] reported that GCF volume is not a reliable parameter reflecting orthodontic treatment-related tissue remodeling. In consistent with the studies indicating no change in GCF volume with orthodontic tooth movements [30, 31] we have found no significant change in GCF volume in all measurements prior to and at different stages of the treatment.…”
Section: Discussionmentioning
confidence: 99%